Public Health Risk Assessment of Antibiotic Residues and Waterborne Pathogens in Drinking Water Sources of Jos North and Barkin Ladi Local Government Areas, Plateau State, Nigeria - Johnpaul O. Amuka,; Chidiebere C. Ezike,; Henderson O. Ogbaji,; Awajiiroijana U. Okpoji,; Agbonma B. Ukaigwe,; Chihurumnanya O. Oji,; Muhammed H. Garuba,; Basil N. Anukam,; Azubuike G. Otuuh,; Gertrude U. Nwafor,; Chidiebere M. Chigbo,; Chukwuemeka F. Nnadozie, (Public Health, 2026)
Antibiotic residues and waterborne pathogens in drinking water systems have become major environmental and public health concerns due to their contribution to antimicrobial resistance and waterborne disease transmission. This study assessed the occurrence of antibiotic residues, microbial contamination, and associated public health risks in drinking water sources from Jos North and Barkin Ladi Local Government Areas of Plateau State, Nigeria. A comparative cross-sectional environmental study design was employed involving forty drinking water samples collected from boreholes, hand-dug wells, streams, and storage tanks. Physicochemical parameters, antibiotic residues, microbial quality, and antimicrobial resistance patterns were analysed using standard laboratory procedures. Results revealed that drinking water sources from Jos North recorded higher physicochemical pollution levels compared to those from Barkin Ladi. Electrical conductivity values were 684.3 ± 21.4 µS/cm and 432.7 ± 18.6 µS/cm, respectively, while turbidity values were 12.6 ± 2.3 NTU and 7.2 ± 1.4 NTU. Ciprofloxacin recorded the highest antibiotic concentration with values of 5.82 ± 0.74 µg/L in Jos North and 2.84 ± 0.41 µg/L in Barkin Ladi. Total coliform counts were 4.7 × 10³ CFU/mL in Jos North and 2.1 × 10³ CFU/mL in Barkin Ladi. Escherichia coli, Salmonella spp., and Vibrio cholerae were isolated from some drinking water sources. Escherichia coli isolates demonstrated the highest resistance to amoxicillin (78.4%) and tetracycline (64.7%). Hazard index values exceeded recommended safety thresholds in Jos North, indicating potential long-term public health risks associated with chronic exposure to antibiotic-contaminated water. The study demonstrated substantial contamination of drinking water sources and highlights the need for improved water treatment, environmental monitoring, and public health intervention strategies.